Dissemination and implementation research in health translating science to practice - Brownson, Ross C.; Colditz, Graham A.; Proctor, Enola Knisley (New York ; Oxford : Oxford University Press, 2012)
The challenges of moving research to practice and policy are universal, and future progress calls for collaborative partnerships and cross-country research. To help propel this field forward, this volume addresses a number of key issues including how to evaluate the evidence base on effective interventions.
Description based on online resource; title from PDF title page (viewed on May 15, 2012).
Includes bibliographical references.
Keywords: Medicine -- Research -- Methodology; Medicine -- Research -- Statistical methods; Selective dissemination of information